CONNOTATIVE MEANING IN THE LITTLE PRINCE BY ANTOINE DE SAINT EXUPÉRY (A SEMANTICS ANALYSIS) - Wongkar, Keysha; Andries, Fivy A.; Posumah, Jenie (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The Little Prince is a well-known children’s literary work that conveys deep philosophical messages through simple language. Understanding how meaning is expressed beyond literal words is important to reveal the emotional, cultural, and social values reflected in the story. This study aims to analyze the emotional, cultural, and social connotations found in The Little Prince using Leech’s (1981) theory of connotative meaning. This research employed a descriptive qualitative approach using document analysis. The data were obtained from selected expressions in the novel and analyzed using Miles, Huberman, and Saldaña’s (2014) qualitative data analysis model, which includes data condensation, data display, and conclusion drawing. The results show that emotional connotations reveal feelings of love, regret, sadness, and attachment; cultural connotations highlight the contrast between children’s imaginative perspectives and adults’ logical thinking; and social connotations emphasize responsibility and meaningful relationships. In conclusion, connotative meaning plays an essential role in expressing the novel’s philosophical messages. These findings contribute to semantic studies and can support the teaching of linguistic and literary interpretation by helping students understand deeper meanings in literary texts.